Lectotypification of Selaginella decomposita (Selaginellaceae) - Góes-Neto, Luiz Armando De Araújo; Assis, Elton Luis Monteiro De; Salino, Alexandre (Phytotaxa, 2016)
During the preparation of the taxonomic treatment of Selaginellaceae from Brazil (Góes-Neto et al. in prep.) we discovered that various Neotropical – particularly Brazilian – species were poorly typified. Of the species assessed, we verified that ca. 20 species already have a lectotype designated inadvertently (see McNeil et al. 2012, Art. 7.10 and 9.23, Prado et al. 2015) by Alston (1936) and Alston et al. (1981) although, these lectotypifications seem to be unknown to most taxonomists working on Selaginella (Góes-Neto et al. in prep.). However, several Neotropical species still lack lectotypification. One of these is Selaginella decomposita Spring (1840: 123), and in accordance with the Articles 9.2, 9.11 and 9.12 of the Melbourne Code (McNeil et al. 2012), we designate a lectotype for this species below.